Early Childhood Attention Battery: Italian adaptation and new expanded normative data. (May 2020) - Coratti, Giorgia; Mallardi, Maria; Coppola, Carolina; Tinelli, Francesca; Bartoli, Mariaelisa; Laganà, Valentina; Lucibello, Simona; Sivo, Serena; Gallini, Francesca; Romeo, Domenico M.; Atkinson, Janette; Braddick, Oliver; et al.
Abstract: Background: The Early Childhood Attention Battery (ECAB) has been used to assess three different components of attention in preschool children, namely, selective, sustained and attentional control. Aim: The aim of the study was: I) to adapt the ECAB to the Italian language; II) to collect Italian reference data using the translated version and III) to expand the available reference data using 6-month age intervals. Study design: The adaptation of the ECAB to Italian language and the collection of Italian reference data was performed in four phases: translation and identification of the manual and subtests that needed adaptation; interobserver reliability and feasibility of the Italian version; application of the Italian ECAB; statistical analysis. Subjects: The ECAB was performed on a low risk population between 3 and 5 years, 11 months. Results: Statistical analysis was conducted subdividing the cohort in 6-month age groups. The final cohort included 300 low-risk typically developing children. The assessment was well accepted and enjoyed by most of the children except for some in the youngest group who refused to complete all of the tests. Our data showed a progressive improvement in attention across age in seven of the eight subtests of the ECAB. Conclusion: The ECAB is a feasible battery in Italian as in the English version, for the assessment of early attention in preschool children, allowing the assessment of the different components of attention and a specific maturation follow up with increasing age. Highlights: Early Childhood Attention Battery is used for the early assessment of attention. The aim of the study was to obtain ECAB normative data in an Italian population. The assessment was accepted by most of the children except for the youngest ones. Our data showed a progressive improvement of the results with increasing age. The ECAB allows the assessment of different attention components and maturation.